Nanoscale T-shaped AlGaN/GaN HEMT with improved DC and RF performance. (29th March 2019) - Mohapatra, Meryleen; De, Tanmoy; Panda, A.K.
AlGaN/GaN-based HEMT with different gate structure are designed i.e., 150 nm rectangular shaped HEMT and 90 nm T-shaped HEMT. It is shown that the DC parameters like drain current, transconductance are improved for T-shaped HEMT as compared to normal gate HEMT. The maximum cut-off frequency for normal gate HEMT is 24 GHz at drain voltage of 20 V and gate voltage of 2 V whereas it is 47 GHz for the T-shaped HEMT. Maximum frequency of oscillation for normal gate HEMT is 95 GHz and for T-shaped HEMT, it is 115 GHz. At the frequency of 5 GHz, the minimum noise figure of the normal gate HEMT is 0.13 dB and for T-shaped HEMT, it is 0.05 dB. Intrinsic time delay of normal gate HEMT is 22 ps whereas the intrinsic time delay for T-gate HEMT is 12 ps. These results prove that the T-shaped HEMT is more preferable for high frequency operations like radar communication, satellite communication, wireless communication, etc.